Assessment of cone beam computed tomography for determining position and prognosis of interradicular mini-implants - Eroncy Souto BATISTA JUNIOR; Ademir FRANCO; Mariana Quirino Silveira SOARES; Monikelly do Carmo Chagas NASCIMENTO; José Luiz Cintra JUNQUEIRA; Anne Caroline OENNING (Dental Press Editora, 2022)
ABSTRACT Objective: To investigate the influence of dynamic visualization of cone beam computed tomography (CBCT) scans on orthodontist's assessment of positioning status and prognosis of interradicular mini-implants (MI). Methods: Three MI positions were virtually simulated in thirty CBCT volumes: (1) MI 1 mm from the lamina dura (LD), (2) MI touching the LD and (3) MI overlapping the LD. Each position was exposed to orthodontists (n = 35) as panoramic reconstruction, sagittal reconstruction and a sequence of axial slices. Each orthodontist evaluated the MI position (relationship with the LD) and scored the prognosis using a four-point scale (the higher the score, the better the prognosis). Kappa, Friedman and Nemenyi statistics were used. Results: Statistically significant associations were detected between the prognosis scores and the type of image visualized (p<0.05). The dynamic visualization of the CBCT volume (axial slices) was associated with higher scores for prognosis and more reliable evaluation of MI positioning. Inconsistent outcomes were more frequently associated with panoramic and sagittal reconstructions. Conclusion: The dynamic visualization of axial slices allowed orthodontists to perform better assessment of MI position and considerably affected prognosis judgment.